A Qualitative Study: Investigating EFL Learners’ Self- Confidence To Decrease The Reticence In Speaking Ability - Ikrar Genidal Riadil (Universitas PGRI Yogyakarta, 2020)
Language is a pivotal aspect of human being. By learning, language people can communicate with each other, get information from one to another and interact. Unfortunately, in the real condition, it is still difficult for Indonesian students to practice their English ability in daily conversation. This study deals to increase the English as a Foreign Language (EFL) students' confidence in English speaking. This research used qualitative analysis by distributing questioner. This study suggest that EFL teachers should seek ways to increase students' collaboration in the classroom to help them gain confidence in speaking. The study involved the students in the fifth semester in the English Department at Tidar University. The researcher compared the gathered data with other relevant researches and theories involved in the study. Based on the research questions, the research result shows that students’ perceptions of self-confidence have a significant to decrease reticence in speaking skills. However, lecturers need to push the students in practice speaking English in front of a class, especially to improve the self-confidence when the students are communicating in English. Two research questions were formulated in this study. There are: (1) what are the factors of the EFL students’ reticence in speaking? (2) Do the students have high self-confidence in speaking skills? In conclusion, this article showed the results that EFL Learners’ self-confidence can be decreased the reticence in speaking ability or not. keywords: Self-confidence, speaking ability, EFL students, qualitative study